Feasibility of solar photovoltaic and wind power distributed generation with battery energy storage systems in light of regulatory framework and economic incentives - Doile, Gabriel Nasser Doyle de (2021)
The worldwide claim for reduced consumption of fossil fuels has highly grown up in recent decades because the burning process of these fuels is one of the greenhouse effects causes. In line with this, the production of electricity from renewable sources has grown exponentially in many countries, including Brazil. Even though the Brazilian electricity matrix is essentially hydraulic, the growth of renewable sources follows the same worldwide pattern. The main difference is that, in Brazil, energy storage is still very incipient, except that one from hydropower reservoirs. Not even the regulation of the electricity sector is prepared to encourage the insertion of new devices for energy storage. This dissertation is organized into chapters that, apart from the first and the last one, gave rise to scientific articles, which analyse and seek to present solutions for specific gaps and incentive ways for the sustainable growth of distributed generation from wind and solar photovoltaic sources, with energy storage. The first chapter presents the general introduction and the main research methods. Whereas the second chapter deals with a systematic literature review, legislation, and regulations applied to the subject. The main finding of this study is that there is very little research on the three themes together and even less on legal and regulatory aspects. Legal and regulatory incentives vary widely among the countries surveyed, but they serve as insight to the Brazilian regulator and legislators. The third chapter deals specifically with the changes in regulation, proposed by ANEEL, and their effects on the already consolidated generation distributed from photovoltaic solar sources. The conclusion points to a significant reduction in these projects' economic viability. In the fourth chapter, energy storage was inserted where, based on the literature review, it was decided to use a battery bank, a more economical alternative for the studied proposal. Although storage brings the economic advantage, as it reduces grid consumption during peak hours when the tariff is more expensive, the business proved to be unfeasible due to the hight batteries’ costs. Given the natural complementarity of wind and solar photovoltaic generation, in the fifth chapter, this source was introduced, which is not yet widespread in Brazil for distributed installations. Considering international prices of wind microturbines, without the import tax, these installations proved to be economically viable and may be the alternative that will give economic viability to distributed generation after the end of the cross subsidy proposed by ANEEL, if there are incentives and/or exemptions tax for the purchase and/or import of batteries and wind microturbines. The main conclusion, presented in chapter 6, is that there is still a need for economic and financial incentives for the feasibility of distributed generation from wind and solar photovoltaic sources, with energy storage, in countries with not well-developed distributed energy systems, as Brazil.